Whole-Virome Analysis Sheds Light on Viral Dark Matter in Inflammatory Bowel Disease - Clooney, Adam G.; Sutton, Thomas D.S.; Shkoporov, Andrey N.; Holohan, Ross K.; Daly, Karen M.; O’Regan, Orla; Ryan, Feargal J.; Draper, Lorraine A.; Plevy, Scott E.; Ross, R. Paul; Hill, Colin (Cell host & microbe, 2019)
The human gut virome is thought to significantly impact the microbiome and human health. However, most virome analyses have been performed on a limited fraction of known viruses. Using whole-virome analysis on a published keystone inflammatory bowel disease (IBD) cohort and an in-house ulcerative colitis dataset, we shed light on the composition of the human gut virome in IBD beyond this identifiable minority. We observe IBD-specific changes to the virome and increased numbers of temperate phage sequences in individuals with Crohn’s disease. Unlike prior database-dependent methods, no changes in viral richness were observed. Among IBD subjects, the changes in virome composition reflected alterations in bacterial composition. Furthermore, incorporating both bacteriome and virome composition offered greater classification power between health and disease. This approach to analyzing whole virome across cohorts highlights significant IBD signals, which may be crucial for developing future biomarkers and therapeutics. [Display omitted] •Analyzing viral dark matter changes our understanding of the gut virome•Gene-based clustering can address the challenges of high inter-individual variation•Healthy human gut virome is dominated by a stable core of virulent bacteriophages•In Crohn’s disease, the virulent core is replaced with temperate bacteriophages In this study, Clooney et al. describe changes in the composition and function of the human gut virome by analyzing both known and unknown viral sequences. They provide evidence that a healthy core of virulent bacteriophage is replaced by temperate bacteriophage in inflammatory bowel disease.